Transformasi Pondok Pesantren dalam Upaya Internalisasi Kompetensi Literasi Digital (Studi: Pondok Pesantren Modern Al-Rifa’I 2, Kabupaten Malang) - Fahrurrosi, Lingga; Ismail Siregar, M. Taufiq; Muzedi, Hesim (Universitas Al-Qolam Malang, 2025)
This study examines the transformation of Pondok Pesantren Modern Al-Rifa'i 2 in internalizing digital literacy competencies. Using a qualitative approach with a case study method, this study aims to analyze the pesantren's strategies in integrating digital literacy into the curriculum and culture, as well as identifying the challenges faced. Data was collected through in-depth interviews, participatory observation, and document analysis, then analyzed using the Miles and Huberman model and triangulation. The results of the study indicate that the boarding school has integrated digital literacy into its vision, programs (“Media Al-Rifa'i” for the creation of Islamic content), and curriculum (ICT, digital Project Based Learning). There has been a shift in teaching methods from conventional to the use of digital media. The central role of teachers as facilitators and supervisors of digital ethics is supported by external assistance. The main challenge is maintaining a balance between the values of the pesantren and the digital world. The pesantren plans to incorporate digital literacy into its long-term curriculum, preparing students for the digital age without compromising moral values. It is hoped that this research can serve as a reference and encourage further research on the adaptation of Islamic educational institutions to the digital age.